Trends of Outdoor Thermal Discomfort in Mymensingh: an Application of Thoms’ Discomfort index - Talukdar, MSJ; Hossen, MS; Baten, MA (Journal of Environmental Science and Natural Resources, 2018)
Thermal comfort is considered very important in aspects of risk assessment, summertime morbidity or in building designing. The present study applied Thom’s discomfort index (DI) to assess the trend of outdoor thermal discomfort in Mymensingh City during 2006-2015. It wasfound that December to February months was comparatively comfortable, DI values were typically <21 and therefore no people felt any discomfort in these months. On the other hand, under 50% population experienced discomfort during March and November months when discomfort valueswere ranged between 21- 24. From April to October months discomfort values varied from 25-27, which indicated thatover 50% population suffered from discomfort in this period. Though no extreme discomfort condition observed in Mymensingh city, the results revealed from June to September months most of the population suffered from severe discomfort in Mymensingh city due to the high air temperature, and high relative humidity. J. Environ. Sci. & Natural Resources, 10(2): 151-156 2017